1983
DOI: 10.1103/physrevd.27.2776
|View full text |Cite
|
Sign up to set email alerts
|

Study of diquark fragmentation intoΛandY*+inνnand

Abstract: We apply a new method to determine the probability of the uu diquark from vp interactions fragmenting as independent quarks. In particular, by assuming that all 12's which do not come from Y*', N*', or charmed baryons must come from independent fragmentation, we show this probability to be about 50%. We also provide information from v n interactions on the fragmentation of ud diquarks into A's, and from this determine the probability of capturing a strange quark from the sea in the target region to be 7 , = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…It is clear that the phases will be functions of r and α, and that CP violation is characterized by y = r sin α, with r ∼ O(m b /m t ). This fact led the authors of [10,4] to calculateK in a linear expansion in y. Later on, in [8], the full solutions for the phases for mixing between the first two generations were calculated and it was found that the linear approximation works perfectly well for these entries.…”
Section: Quark Mixingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that the phases will be functions of r and α, and that CP violation is characterized by y = r sin α, with r ∼ O(m b /m t ). This fact led the authors of [10,4] to calculateK in a linear expansion in y. Later on, in [8], the full solutions for the phases for mixing between the first two generations were calculated and it was found that the linear approximation works perfectly well for these entries.…”
Section: Quark Mixingmentioning
confidence: 99%
“…Hence the SM limit of the SB-LR is inconsistent by 3.5 σ with current experiments. This has the important consequence that the SB-LR is actually testable, and distinct from the SM: experimental bounds cannot be indefinitely evaded by simply sending the R sector to infinite masses: scalars and vectors in the range (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) TeV are definitely needed.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum deviation from the SM prediction a CP = 0 is obtained if σ 1 = π − σ 2 = π/2 + δ D implying (Ā/A) max = e 0.85i and |a (s) max CP | = 0.85. Next we consider the decays (17) which have the feature of having only one isospin channel describing a ∆I = 1 transition. Consequently QCD penguins cannot contribute to the processes.…”
Section: New Physics In Decay Amplitudesmentioning
confidence: 99%
“…In this paper we study the possible new physics effects in CP asymmetries in two body B s decays in the LRSM with spontaneous CP violation [17,18]. In this model there are new CP phases which are unsuppressed for the third family and thus may affect B s system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation